Postoperative Esophagectomy Management in Intensive Care Unit: Cooperation and Comorbidities - D. Sutedja, Anasthasia; Manggala, Sidharta K. (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2024)
Esophagectomy remained a high-risk and high-mortality surgery for patients with esophageal carcinoma, with a rate of morbidity of up to 65% and a 30-day mortality of up to 4%. Although many have described intraoperative management of such patients, long-term and comprehensive analysis of postoperative anesthesia management was limited due to chronic and arduous follow-up throughout intensive care. We present a case of a 64-year-old male in the intensive care unit (ICU) after undergoing esophagectomy and gastric pull-up performed by digestive and thorax surgeons. The patient was found with sputum retention, inadequate cough, and desaturation after stepping down to the ward. Reintubation was done, and the patient was readmitted to ICU. During the second admission, relaparotomy successfully repaired the leakage, but trial extubation was unsuccessful. The patient developed sepsis due to ventilator-associated pneumonia. Tracheostomy was considered and dismissed as there was a high risk of descending pulmonary infection. The patient was signed up for palliative care, and during his last days, the family decided not to resuscitate him. After one month of intensive care, the patient succumbed to his illness. Optimizing patient care in the ICU should include fluid, nutrition, pain, and respiratory management. Multispecialty team approach was essential, with an anaesthesiologist acting as a moderator in managing pain, stress, hemodynamics, ventilation, enhanced recovery, early detection, and management of complications.